Digitalization of Arabic language learning in rural contexts: opportunities, challenges, and philosophical dilemmas - Muzakki; Kamal Yusuf; Ahmad Dzulkifli Rif’at (At Turots: Jurnal Pendidikan Islam, 2025)
The digitalization of education has created new opportunities and challenges, particularly in rural contexts where infrastructure, resources, and cultural factors shape learning practices. While existing studies have emphasized the technical and pedagogical dimensions of digital learning, little attention has been given to the lived experiences and philosophical dilemmas surrounding the digitalization of Arabic language education in rural schools. This study addresses this gap by exploring opportunities, challenges, and philosophical tensions in the digital implementation of Arabic learning at Madrasah Ibtidaiyah Miftahul Falah Jepara, Indonesia. Employing a qualitative case study with a phenomenological orientation, data were collected over three months (June–August 2025) through classroom observations, semi-structured interviews with teachers and students, and focus group discussions with school stakeholders. The findings reveal three major opportunities of digitalization: broader access to learning resources, increased student motivation, and pedagogical innovation. At the same time, significant challenges emerged, including limited infrastructure and unstable internet connectivity, financial constraints affecting access to devices, and teachers’ limited digital competence. Beyond these practical issues, the study identified philosophical dilemmas such as the reduction of cultural and spiritual values and tensions between modernization and tradition. The study concludes that digitalization in rural Arabic education must be understood not only as a technical process but as a socio-cultural transformation requiring hybrid approaches that integrate technology with traditional values. Recommendations include teacher professional development, context-sensitive policies, and culturally responsive digital platforms.